DAKSA MEDICAL LABORATORY BUSINESS DEVELOPMENT PROJECT PLANNING AND OPERATIONAL STRATEGY - Elson, Morten; Syah, Tantri Yanuar Rahmat; Indradewa, Rhian; Sunaryato, Ketut (Journal of Economic, Business and Engineering (JEBE), 2024)
Building a Medical Laboratory business in Bekasi district requires operational process planning according to plan. Therefore, it is necessary to analyze operational plans in business development and long-term strategies that are appropriate to achieve the business objectives of developing Daksa Laboratory. The purpose of this research is to analyze the company's operational plans in developing the Medical Laboratory Business. This research uses qualitative research methods. Data collection techniques in this research use literature study, interviews and observation. The data collected was then evaluated and analyzed thematically. The results of the research show that the operational plan for developing the Daksa Medical Laboratory business has been well prepared. This operational planning is carried out through several stages of selecting the construction site, service facility infrastructure, service planning and operational implementation programs.